Ciało i jego fragmenty w prozie Mikołaja Gogola - Witczak, Krzysztof (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The article presents a perspective of somatic present in the prose of Nikolai Gogol. The body is treated here as a project — a collection of body fragments. Particular attention is paid to the figure of nose, which occurs in two selected short stories entitledNose and Diary of a Madman. Therefore, any attempt to emancipate the body part is a threat to the need to preserve the face. Nose is a sense of belonging. This part of the body is thus a limit to what we used to be referred to as belonging to us. Its location creates the last bastion of perception, the selfness.